Effect of Credit Risk on Profitability of Nepalese Commercial Banks - Shrestha, Purna Man (Butwal Campus Journal, 2022)
This paper has examined the effect of credit risk on profitability of Nepalese commercial banks. The credit risk is measured by the ratio of total loan to total deposit (TL/TD), cash reserve ratio (CRR), the ratio of nonperforming loan to total loan (NPL/TL), and the ratio of loan loss provision to total loan (LLP/TL), and profitability is measured by return on assets (ROA). The annual data of 18 commercial banks from 2013/14 to 2018/19 have been used for the analysis. Using the Fixed Effect model, this paper finds the significant influence of credit risk on profitability of Nepalese commercial banks. Finally, it is observed that TL/TD has significant positive and NPL/TL and LLP/TL has significant negative impact on profitability of Nepalese commercial banks. Therefore, the bank management should increase the ratio of total loan to total deposit and should decrease the ratio of nonperforming loan to total loan and loan loss provision to total loan to increase the profitability of Nepalese commercial banks.